Leisure among university students in the healthcare area: a review of the literature - Vieira, Julia Lelis [UNESP]; Romera, Liana Abrao; Pereira Lima, Maria Cristina [UNESP] (Abrasco, 2018)
This article set out to analyze studies on leisure activities among university students in the healthcare area. It conducted a search using the following key words: leisure and students, and their corresponding terms in Spanish and English in the Bireme database, which resulted in 32 articles at the end of the review. In the articles analyzed there was a predominance of the following leisure interests: sports, social, intellectual and artistic activities, with a greater number of articles presenting experiences in sports. It was also noted that the intake of alcohol in the leisure context is often mentioned by this population group. There was a predilection for physical exercised/sport during leisure time, compared to other leisure interests and little knowledge about any other possibilities for leisure. This article also discusses the need to develop strategies that promote leisure among these students, seeking to improve their quality of life. It is noteworthy that they are health professionals in the training phase and it is quite possible that their future orientations might be influenced by their personal practices.
Keywords: Leisure activities; Students; Mental health; Alcohol abuse